the Development of an SMAW Welding Textbook to Enhance Student Engagement and Cognitive Abilities - Agustien, Gina; Abdillah, Hamid; Abizar, Haris (Universitas Negeri Semarang, 2025)
This study aims to develop a Shielded Metal Arc Welding (SMAW) textbook to enhance student engagement and cognitive abilities, assess its feasibility, and evaluate its impact on learning outcomes. The research employs a Research and Development (R&D) approach using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The subjects included 32 Grade XI TPL students at SMKN 2 Kota Serang, along with one media expert and one material expert as validators. Data were collected through expert validation questionnaires, student response questionnaires, engagement observation sheets, and pretest–posttest assessments. The developed textbook is aligned with the Indonesian National Work Competency Standards (SKKNI) and structured using a Problem-Based Learning (PBL) approach, complemented by Welding Procedure Specifications, job sheets, run sheets, and visual assessment rubrics. The feasibility results indicate a fair rating from the media expert (64%) and a high rating from the material expert (94%). Student responses were very positive (83%). Cognitive improvement reached a moderate level (N-Gain = 0.6), and student engagement was categorized as very active (76%), indicating the textbook’s effectiveness as a learning medium.